Prevalence and bacteriological profile of neonatal sepsis in newborn intensive care unit of a tertiary care hospital in Central India - Minarey, Naikey; Gornale, Vinod Kumar; Singh, Karan Bahadur; Ghosh, Newton; Shrivastava, Priyanka (Indian Journal of Child Health, 2019)
Background: Neonatal sepsis (NS) is the most common cause of neonatal mortality responsible for about 30–50% of total neonatal deaths in developing countries. Surveillance of causative organisms and their antibiotic sensitivity pattern promotes the rational use of antibiotics and antibiotic stewardship. Objectives: The objectives of this study were to study the prevalence of NS in newborn intensive care unit of a tertiary hospital of Central India and to isolate the most common organism involved in sepsis in our setting. Materials and Methods: A retrospective study was conducted and relevant data of the neonates diagnosed with culture-positive sepsis were obtained from the case records during the period from February 2018 to February 2019. Culture-positive sepsis was defined as the isolation of bacterial pathogen from blood in neonates with clinical suspicion of sepsis. Results: A total of 223 neonates were enrolled. The major morbidities were hyperbilirubinemia (23.3%), birth asphyxia (14.3%), sepsis (53.8%), and respiratory distress (32.7%). The main causes of neonatal mortality were birth asphyxia (9.8%), prematurity (18.83%), sepsis (32.23), hyaline membrane disease (13.4%), and meconium aspiration syndrome (13.9%). A total of 120 cultures were found to be positive. The most common organism isolated was Staphylococcus aureus (39.3%) followed by Klebsiella pneumoniae (34%). Candida albicans was also isolated. Conclusion: Culture-positive NS accounted for 53.8% of all cases and is the major cause of mortality (32.28%) in the present study. Sepsis caused by Gram-positive bacteria was the most common among the neonates, although mortality was more in Gram-negative sepsis. Therefore, empirical regimen should be modified based on antibiogram of the isolates.